Avaliação de língua portuguesa em provas escolares do século XX (1935 e 1963) - Arena, Dagoberto Buim [UNESP]; Arena, Adriana Pastorello Buim (My University, 2013)
The article analyses three school exams of Elementary School, two belonging to a mother and one of her son, which were kept and provided to the researcher by the mother. The first two exams were dated March 30 and November 13, 1935 of the 3rd grade of Grupo Escolar Fernando Lobo in Juiz de Fora, Minas Gerais. The third one was produced at Grupo Escolar Coronel Amâncio Bueno in Jaguariúna, São Paulo in March 28, 1963 in a 4th grade class. The analysed data all together point out school products which are the result of the relationship between teacher, student and school culture. School exams are as important documents as the notebooks in order to understand the school culture, and as this paper tries to indicate, they are the means for the insertion into the world of written culture. The methodology based on the microanalysis of these documents reveals records about the structure of the exams and the Brazilian school curriculum in the teaching of Portuguese as a mother tongue in 1935 e 1963.

O artigo analisa três provas escolares do ensino primário, duas de uma mãe e uma de seu filho, guardadas e fornecidas ao pesquisador pela mãe. As duas primeiras são de 30 de março e de 13 de novembro de 1935, do 3º. ano do Grupo Escolar Fernando Lobo, em Juiz de Fora, MG. A terceira foi produzida no Grupo Escolar Coronel Amâncio Bueno, em Jaguariúna, SP, em 28 de maio de 1963, em classe de 4º. ano. O conjunto dos dados analisados destaca produtos escolares resultantes das relações entre professor, aluno e cultura escolar. As provas são documentos tão importantes quanto os cadernos para compreender os produtos da cultura escolar e, como este artigo quer indicar, são meios para a inserção no mundo da cultura escrita. A metodologia de microanálise dos documentos revela registros sobre a estrutura das provas e o currículo da escola brasileira no ensino do português como língua materna em 1935 e 1963.

Para realizar este trabajo se examinaron tres pruebas escolares de enseñanza primaria, dos de una madre y una de su hijo, proporcionadas al investigador por la primera. Las dos pruebas pertenecientes a la madre son del 30 de marzo y del 13 de noviembre de 1935, correspondientes al 3° año de la Escuela Fernando Lobo, en Juiz de Fora, MG. La tercera, fue realizada por su hijo en la Escuela Coronel Amancio Bueno en Jaguariúna, SP, el 28 de mayo de 1963, en una clase de 4° año. Del análisis de estos antecedentes escolares, surgen datos acerca de las relaciones entre el maestro, el estudiante y la cultura escolar. Las pruebas, como así también los cuadernos, permiten entender la cultura y los frutos de la escuela. Este trabajo pretende resaltar la importancia de la misma en la inserción en el mundo de la cultura escrita. La metodología para el microanálisis de los documentos revela los registros de la estructura de las pruebas y el currículo escolar en la enseñanza del portugués brasileño como lengua materna en 1935 y 1963.
Evaluación de la lengua portuguesa en pruebas escolares del siglo XX (1935 e 1963)
Evaluation of the portuguese language in scholars exams in the twentieth century (1935 and 1963)